2020
DOI: 10.3389/fnins.2019.01442
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Testing of Bionic Peripheral Nerve and Muscle Interfaces: Animal Model Considerations

Abstract: Introduction: Man-machine interfacing remains the main challenge for accurate and reliable control of bionic prostheses. Implantable electrodes in nerves and muscles may overcome some of the limitations by significantly increasing the interface's reliability and bandwidth. Before human application, experimental preclinical testing is essential to assess chronic in-vivo biocompatibility and functionality. Here, we analyze available animal models, their costs and ethical challenges in special regards to simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
(54 reference statements)
0
14
0
Order By: Relevance
“…[30,31,[37][38][39] There are no data in using electroneuronography (ENG) instead of EMG in external prosthesis control; for completely substituting a muscle, ENG could be more useful if the natural muscle must be surgically excised making impossible to have an EMG signal; in this case, ENG sensors should be used. [112,113] As described previously, use of a wireless amplification system to communicate with an external prosthesis (residual muscle activation signal-sensorwireless communication with amplifier-signal amplificationexternal prosthesis controller) can reach a sufficient voltage to actuate the external myoelectric prosthesis. [48][49][50][51] This same approach should be applicable to artificial muscles implants.…”
Section: Combining Current Technologies For a Clinical Applicationmentioning
confidence: 99%
“…[30,31,[37][38][39] There are no data in using electroneuronography (ENG) instead of EMG in external prosthesis control; for completely substituting a muscle, ENG could be more useful if the natural muscle must be surgically excised making impossible to have an EMG signal; in this case, ENG sensors should be used. [112,113] As described previously, use of a wireless amplification system to communicate with an external prosthesis (residual muscle activation signal-sensorwireless communication with amplifier-signal amplificationexternal prosthesis controller) can reach a sufficient voltage to actuate the external myoelectric prosthesis. [48][49][50][51] This same approach should be applicable to artificial muscles implants.…”
Section: Combining Current Technologies For a Clinical Applicationmentioning
confidence: 99%
“…There are both ethical and scientific reasons for using animal models; however, these models also lead to several associated translational challenges. A recent detailed review of animal models used for peripheral nerve interface development can be found in Aman et al [90].…”
Section: Experimental Modelsmentioning
confidence: 99%
“…Most of neuroprosthetic development is performed in rodents, often serving as of proof of concept ( Aman et al, 2020 ). Neuroprosthetics with the potential for clinical translation is often tested in larger animals to determine chronic safety and efficacy and ultimately enter human clinical trials.…”
mentioning
confidence: 99%